2017
DOI: 10.1038/srep44632
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Corrigendum: HIPSTR and thousands of lncRNAs are heterogeneously expressed in human embryos, primordial germ cells and stable cell lines

Abstract: This Article contains errors in Figure 5F-J, where the right-hand y axes 'Density (lncRNAs)' are incorrectly given as 'Density

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Some studies reveal that lncRNA GAS5 can inhibit the proliferation of multiple cells and promote their apoptosis, and the action mechanism of these cells forms the basis of tumor inhibition together [ 11 , 12 ]. Yunusov et al [ 13 ] showed in their study that lncRNA expression demonstrated tissue specificity and cell specificity as well as the specificity of eukaryote at developmental stage. lncRNA GAS5 is a member of lncRNA and plays a regulatory role in the development of many acute and chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reveal that lncRNA GAS5 can inhibit the proliferation of multiple cells and promote their apoptosis, and the action mechanism of these cells forms the basis of tumor inhibition together [ 11 , 12 ]. Yunusov et al [ 13 ] showed in their study that lncRNA expression demonstrated tissue specificity and cell specificity as well as the specificity of eukaryote at developmental stage. lncRNA GAS5 is a member of lncRNA and plays a regulatory role in the development of many acute and chronic diseases.…”
Section: Introductionmentioning
confidence: 99%